PERILAKU KONSUMSI PENGGUNA HP ANDROID SAMSUNG DI TOKO NEW ASLISEL KUALA SIMPANG MENURUT PERSPEKTIF EKONOMI ISLAM - Nona, dwi (Fakultas Ekonomi dan Bisnis Islam, 2020)
The purpose of consumption in Islam is not only satisfaction in the world but also the welfare of the hereafter to fulfill needs and not fulfill satisfaction / desires is the goal of Islamic economic activity this is what is also experienced by customers who buy Android phones at New Aslisel Stores with Samsung brands. These consumers use cell phones for the benefit of life activities and not just to improve social status, of course this is inseparable from people's consumption behavior, based on these problems, the researcher wants to examine in this thesis about